PENGARUH PEMBERIAN PMSG DAN HCG TERHADAP PENINGKATAN JUMLAH KELAHIRAN HAMSTER CAMPBELL (Phodopus campbelli) (Effect of PMSG and hCG to Increase Birth Number in Campbell’s Hamsters (Phodopus campbelli)) - Novi Afriani Nur Afriani Nur; Tongku Nizwan Siregar; Hamdan Hamdan; Idawati Nasution; Cut Nila Thasmi; Dasrul Dasrul (Jurnal Medika Veterinaria, 2016)
The aim of this study was to determine the effect of superovulation induction through Pregnant Mare’s Serum Gonadotropin (PMSG) and Human Chorionic Gonadotropin (hCG) injection to increased birth number in Campbell’s hamsters (Phodopus campbelli). This study used 10 unpregnant female Campbell’s hamster, aged 4-6 months, weighing of 25-30 grams. Hamsters were divided into K1 and K2, each consist of five hamsters. K1 injected with 1 ml physiologic NaCl, while K2 intraperitoneally injected with PMSG and hCG in 5 IU. Mating was held after injection. Male and female hamsters were put in one box with ration of 1:1. The observation of vagina plug was done in order to confirm whether the mating successes or not. The average amount of fetus birth through superovulation on K1 and K2 were 3.40±1.3 and 7.80±1.1, respectively. In conclusion, the superovulation induction using the combination of PMSG and hCG increase birth number on Campbell’s hamsters.